Keseimbangan Antara Hak Dan Kewajiban Suami Istri Dalam Hukum Keluarga Islam - Muhammad Fasral Hafid; Hartono Hartono; Achmad Fahruddin (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This research can explore the basic principles that govern the rights and obligations of husband and wife in Islamic family law. This study aims to examine in depth the concept of balancing the rights and obligations of husband and wife in the perspective of Islamic family law. This research uses library research method by collecting and analyzing secondary data. The main data sources include the Qur'an, Hadith, classical and contemporary fiqh books, laws, the Compilation of Islamic Law, as well as various scientific literature, journals, and articles. The results show that Islamic family law pays great attention to the balance of rights and obligations of husband and wife. Although there are differences in roles and responsibilities, both have rights and obligations that must be carried out. The husband's rights include being obeyed and respected by his wife, while his obligations include providing physical and mental sustenance and treating his wife well. The wife's rights include receiving maintenance, good treatment, and protection from her husband, while her obligations include maintaining the honor of herself and her family and managing household affairs.